Assessing the Influence of Leadership Style, Decision Making, Communication, and Team Building on the Success of MSME Entrepreneurial Businesses in Bandung City - Heliza Rahmania Hatta; Edison Hatoguan Manurung; Hefri Yodiansyah; Sukirman Sukirman; Zilfana Zilfana (West Science Business and Management, 2023)
Various factors, including leadership style, decision making, communication, and team building, influence the success of MSME entrepreneurial businesses. This quantitative study aimed to assess the influence of these factors on the success of MSME entrepreneurial businesses in Bandung City, Indonesia. Data were collected through a survey of 150 MSME owners in Bandung City, and multiple regression analysis was used to examine the relationship between the independent variables and business success. The results showed that leadership style and team building significantly predicted business success, while communication and decision-making were not significant predictors. These findings suggest that effective leadership and team building are essential for business success in the context of MSMEs in Bandung City.